Патоморфологічна характеристика епітеліально-мезенхімальної трансформації та стовбурових клітин при прогресуванні протокової аденокарциноми підшлункової залози - Кабаченко, Валерія Олександрівна; Kabachenko, V. O. (Запорізький державний медико-фармацевтичний університет, 2025)
Метою даної роботи було удосконалити патоморфологічну діагностику та прогнозування перебігу протокової аденокарциноми підшлункової залози на основі патоморфологічного та імуногістохімічного аналізу трепанбіопсійного та оперіційного матеріалу. Дисертаційна робота виконана на основі власних досліджень і аналізі отриманих результатів. Проведено мікроскопічне, морфологічне та імуногістохімічне дослідження трепанбіопсійного та біопсійного матеріалу підшлункової залози, отриманого під час операцій, виконаних в період з 2012 по 2020 рр. в хірургічних відділеннях ТОВ «Віта-Центр» м. Запоріжжя, КУ «Міської клінічної багатопрофільної лікарні №3» ЗОР м. Запоріжжя, КУ «Запорізької обласної клінічної лікарні» ЗОР м. Запоріжжя, а також секційний матеріал, як контрольна група, від КУ «Запорізького обласного бюро СМЕ» Запорізької обласної ради. Основну групу склали 139 пацієнтів із протоковою аденокарциномою підшлункової залози (74 трепан-біопсій, 65 зразків операційного матеріалу. Контрольна група – 10 зразків аутопсійного матеріалу. Вік пацієнтів основної групи коливався в діапазоні 36-84 роки, середній склав 61,68±7,75 років. Вік пацієнтів контрольної групи 56-73 роки, середній вік – 64,5±2,33 років. The aim of this work was to improve the pathomorphological diagnostics and prediction of course of pancreatic ductal adenocarcinoma based on pathomorphological and immunohistochemical analysis of trepanobiopsy and surgical material. The dissertation work was carried out on the basis of own research and analysis of the obtained results. Microscopic, morphological and immunohistochemical study of trepanobiopsy and biopsy material of the pancreas obtained during operations performed in the period from 2012 to 2020 in the surgical departments of LLC "Vita-Center" Zaporizhzhia, KU "City Clinical Multidisciplinary Hospital No. 3" ZOR Zaporizhzhia, KU "Zaporizhzhya Regional Clinical Hospital" ZOR Zaporizhzhia, as well as from KU "Zaporizhzhya Regional Bureau of SME" of the Zaporizhzhia Regional Council. The main group consisted of 139 patients with pancreatic ductal adenocarcinoma (74 core biopsies, 65 samples of surgical material. The control group consisted of 10 samples of autopsy material. The age of the patients in the main group ranged from 36 to 84 years, the average was 61,68±7,75 years. The age of the patients in the control group was 56-73 years, the average age was 64,5±2,33 years. Depending on the size of the tumor, two groups were distinguished: Group I - tumors less 3 cm (51 cases), Group II - tumors more 3 cm (88 cases). Each group was divided into subgroups depending on the degree of differentiation: subgroup Ia - tumors with a moderate (G2) level of differentiation (35 cases), subgroup Ib - tumors with a low (G3) level of differentiation (16 cases); subgroup IIa - tumors with a G2 level differentiation (34 cases), subgroup IIb - tumors with G3 level of differentiation (54 cases). Degrees of differentiation G1 and G4 were excluded due to small samples.
Pathomorphological characteristics of epithelial-mesenchymal transformation and stem cells in the progression of pancreatic ductal adenocarcinoma
Keywords: підшлункова залоза; протокова аденокарцинома; епітеліально-мезенхімальна трансформація; Е-кадгерин; β-катенін; цитокератин 7 (СК7); цитокератин 18 (СК18); α-SMA (гладко-м’язовий актин); віментин (Vim); CD44; EpCAM; імуногістохімічне дослідження; цифрова морфометрія; pancreas; ductal adenocarcinoma; epithelial-mesenchymal transformation; E-cadherin; β-catenin; cytokeratin 7 (CK7); cytokeratin 18 (CK18); α-SMA (smooth muscle actin); vimentin (Vim); immunohistochemical study; digital morphometry